Corporate ethics as a modern instrument for the implementation of state personnel policy - Shchetkina, Marianna A.; Labeyko, Olga A.; Yurashevich, Nadezhda M. (Journal of the Belarusian State University. Sociology, 2026)
The article reveals the substantive aspect, systematises general and specific principles, describes the functions (managing employee behaviour, creating a positive image and social responsibility of the organisation, self-organisation of the professional community, developing corporate culture) of corporate ethics. Corporate ethics is considered not only as a personnel technology of the organisation, but as an effective tool for implementing the state personnel policy. A new function of corporate ethics for the development of human resources, the need to use the principle of citizenship and the principle of patriotism as guidelines for regulating the corporate behaviour of employees are substantiated. Based on the functional approach, a new definition of the concept of «corporate ethics of an organisation» is given.
Keywords: corporate ethics; moral principles and norms; functional approach; personnel policy; personnel potential; citizenship; patriotism